PLASTIC SURGERY MEDICAL TOURISM IN SOUTHEAST ASIA: MARKET DYNAMICS, DESTINATION STRATEGIES, AND INDONESIA'S COMPETITIVE POSITION - Anak Agung Istri Ayu Detritha Sarasmartha Putri; Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; Gede Wara Samsarga; Shita Diwyani Sudarsa; Astri Lestari Suyata (Jurnal Rekonstruksi dan Estetik, 2026)
Highlights: Plastic surgery medical tourism is driven by lower costs, shorter waiting times, quality care, and the appeal of combining treatment with travel. Thailand, South Korea, and Malaysia lead through strong government support, international accreditation, and integrated services. Indonesia, especially Bali, has strong potential but needs improvements in accreditation, language skills, and coordinated national promotion. Abstract: Introduction: Medical tourism has become a rapidly growing global industry, and plastic surgery medical tourism has gained substantial popularity due to cost advantages, accessibility, perceived quality of care, and the opportunity to combine treatment with leisure travel. This review focuses on plastic surgery medical tourism in Southeast Asia, with South Korea included as a non–Southeast Asian benchmark because of its advanced development in this field. Methods: This narrative review synthesized peer‑reviewed articles, policy documents, and institutional reports (e.g., WHO, ISAPS, JCI) published from 2010–2025. Literature was searched in December 2025 using PubMed and Google Scholar, followed by a four‑stage screening process. A thematic comparative analysis was conducted across three Southeast Asian destinations (Thailand, Malaysia, and Indonesia), with South Korea serving as a benchmark market for plastic surgery medical tourism. Results: Plastic surgery medical tourism is mainly driven by cost, shorter waiting times, accreditation and quality assurance, specialist availability, and integration of healthcare with tourism services. Within Southeast Asia, Thailand and Malaysia lead through stronger coordination, branding, and streamlined patient pathways, while South Korea exemplifies a highly coordinated, branding‑intensive model. Indonesia, especially Bali, has strong potential with competitive pricing and tourism appeal but faces challenges in governance, accreditation, and patient navigation. Conclusion: Plastic surgery medical tourism represents a strategic opportunity for economic and health sector development. Strengthening government involvement, international promotion, hospital accreditation, infrastructure, and human resource capacity is essential to enhance competitiveness and sustainability.